FLOOD HAZARDS ASSESSMENT AND RESIDENTIAL FLOOD DAMAGE MAPPING IN HITOYOSHI PREFECTURE, JAPAN - Arbi Surya Satria Ridwan; Riken Homma; Hang Liu (Journal of Architecture&ENVIRONMENT, 2022)
Natural disasters are one of the things that have risks and hazards to the population. This study aims to simulate the flood hazard and calculate its impact on the Hitoyoshi area, Japan residential areas. Hitoyoshi was chosen as the case study because the area experienced a catastrophic flood in 2020 that destroyed the city. The calculation of the impact of this study is also based on mapping the area based on land function, damage to buildings, and building materials, especially in areas affected by floods in the city of Hitoyoshi, Kumamoto. The results of this study indicate how much risk will be caused by flooding, especially in the Hitoyoshi area, with simulations carried out in ArcGIS software. In addition, the simulated hazard map is overlaid with buildings to determine the impact caused by the Hitoyoshi Area. This research aims to provide input for the Japanese institution in increasing the risk of natural disasters against floods, especially in the Hitoyoshi area, in dealing with future disasters. Simulations carried out in areas that have been affected by flooding by making a hazard map and validating it to prove the accuracy of the data are expected to be used and applied in several other countries besides Japan.